Pengaruh Green Marketing Communication terhadap Green Behaviour (Studi Kasus Pemberdayaan Penggunaan Kantong Plastik pada konsumen Alfamart di Kota Bandung) - Saphira, Tasya; Nurtjahjadi, Edi (Universitas Batanghari, 2024)
Plastic waste is a major problem in environmental pollution, both on land and at sea. Indonesia is ranked second in producing plastic waste in the world's oceans. The Ministry of Environment and Forestry stated that plastic waste generated from 100 retail stores or members of the Indonesian Retailers Association (APRINDO) reached 10.95 million pieces of plastic waste within one year. The Ministry of Environment and Forestry (KLHK) created a paid plastic bag policy to address the plastic waste problem. The aim of this research is to determine the influence of green marketing communication on green behavior regarding empowering the use of plastic bags among Alfamart consumers. The data collection technique used was purposive sampling which is included in non-probability sampling with a total of 100 respondents who had used paid plastic bags at Alfamart in Bandung City aged 17 years and over. The empirical data in this research was collected using a one-shot study approach and then processed and analyzed using simple regression using SPSS version 26. The results of the research show that green marketing communication has a positive effect on green behavior. Therefore, Alfamart management can prioritize improving all the indicators that make up green marketing communication because it is hoped that this can have a positive impact on green behavior.